Metabolite profiling of Mexican lime (Citrus aurantifolia) leaves during the progression of witches' broom disease. (September 2015) - Mollayi, Saeed; Zadali, Reza; Farzaneh, Mohsen; Ghassempour, Alireza
Graphical abstract: Highlights: Metabolite profiling of Mexican lime during the progression of WBDL. Among 40 metabolites, 13 showed differences after inoculation with pathogen. The ratio of proline to changed metabolites could be as biomarkers of WBDL in plant. Infected by Ca. Phytoplasma aurantifolia, activate the defense response. Abstract: Witches' broom disease of Mexican lime (WBDL), caused by ' Candidatus: Phytoplasma aurantifolia ', is a big threat to lime production in southern Iran. In this research work, metabolite profiling of Mexican lime was monitored during WBDL progression (6 months) by gas chromatography–mass spectroscopy (GC–MS), to study the effect of Ca. P. aurantifolia infection on lime, as well as to distinguish infected from healthy limes. The principal components analysis (PCA) plot revealed a clear distinction between the leaf metabolite profiles of healthy and infected plants during the progression of WBDL. Results showed that among the 40 different metabolites, including amino acids, organic acids, sugars and sugar alcohols, and fatty acids, only 13 metabolites (such as proline, arginine, glutamate, salicylate, citrate, fructose, inositol and some TCA cycle intermediate) increased significantly after 30 days of inoculation with Ca. P. aurantifolia . In addition, the concentration ratio of some compounds were monitored, (especially the ratio of proline to arginine, alanine, fructose, citrate, 2-oxoglutarat, and succinate), which could act as considerable indicators to diagnose the infected lime at the early stages of the WBDL progression. Our results provide the first metabolome view on the molecular basis of the infection process and identify metabolites that could help inhibit the effects of the pathogen.